2020
DOI: 10.1177/0018578720970470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pharmacy Practice in Hospital Settings in Jeddah City, Saudi Arabia: Dispensing and Administration—2019

Abstract: Purpose: To evaluate the dispensing and administration processes in hospital settings in Jeddah city, Saudi Arabia. Method: A questionnaire based on the annual ASHP national survey was distributed among 35 hospitals. The response rate was 60%. After a follow-up period of 6 months, the final questionnaire was collected in November 2019. Result: The survey had a 60% response rate. Most surveyed hospitals have centralized pharmacies (76.2%). Few hospitals reported the use of the Bar Code Medication Administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…One of those few papers was published in 2012, showing that only three hospitals in Riyadh were using ADCs integrated with the pharmacy system [16,20]. Another paper reported that in 2019, only 28.6% of Jeddah hospitals used ADCs [21]. This technology is relatively new here, yet the number of ADCs has increased over the years [11,16].…”
Section: Adcs In Saudi Arabiamentioning
confidence: 99%
“…One of those few papers was published in 2012, showing that only three hospitals in Riyadh were using ADCs integrated with the pharmacy system [16,20]. Another paper reported that in 2019, only 28.6% of Jeddah hospitals used ADCs [21]. This technology is relatively new here, yet the number of ADCs has increased over the years [11,16].…”
Section: Adcs In Saudi Arabiamentioning
confidence: 99%